2018
DOI: 10.20460/jgsm.2019.268
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Interplay Between Economic Growth and Health Expenditures: The Case of Emerging Economies

Abstract: In emerging countries, health investments are increasing rapidly along with the opportunities provided by economic growth. Examination of the relationship between the efficiency of investments made, in other words, the efficiency of health expenditure-EHEand economic growth is the main purpose of the study. The study was carried out on BRICS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…Our study confirms the results of the papers of Gok et al (2018), Atems (2019), and Modibbo and Saidu (2020) which claim that economic growth has positive impact on health expenditure. As far as the impact of per capita carbon dioxide emissions is concerned on health expenditure, our result is confirmed from mixed results from papers such as Oyelade et al (2020) showing a positive relationship, whereas the paper of Akbar et al (2021) show a bilateral relationship between these two variables.…”
Section: Constantsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirms the results of the papers of Gok et al (2018), Atems (2019), and Modibbo and Saidu (2020) which claim that economic growth has positive impact on health expenditure. As far as the impact of per capita carbon dioxide emissions is concerned on health expenditure, our result is confirmed from mixed results from papers such as Oyelade et al (2020) showing a positive relationship, whereas the paper of Akbar et al (2021) show a bilateral relationship between these two variables.…”
Section: Constantsupporting
confidence: 92%
“…Moreover, Piabuo and Tieguhong (2017) showed that increased spending on health increases human capital productivity and contributes positively to economic growth. Gok et al (2018) examined the connection between the efficiency of health expenditure and economic growth in emerging economies during the period from 2008 to 2012. The study revealed that economic growth can substantially enhance the efficiency of health expenditure in the countries analyzed.…”
Section: Healthcare Expenditure and Economic Growthmentioning
confidence: 99%
“…Gok et al ( 2018 ) study the relation between healthcare expenditure and economic growth in emerging BRICS countries as well as Mexico, Indonesia, South Korea, and Turkey from 2008 to 2012. Healthcare expenditure was used as the only input criterion on DEA model (a linear programming technique).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is almost impossible to overlook the effects of human health on economic growth (Akingba et al, 2018). Most studies have confirmed that health expenditure has a positive impact on economic growth (Modibbo and Saidu, 2020;Atems, 2019;Gok et al, 2018). Meanwhile, some studies show that this relationship is not a one-way relationship.…”
Section: Empirical Studies In Health Expenditure and Economic Growthmentioning
confidence: 99%